EVALUATION OF AVAILABILITY OF A TELECOMMUNICATION SYSTEM WITH DIFFERENT TYPES OF FAILURES - Уланський, В. В.; Терентьєва, І. Є.; Мачалін, І. О. (Science-based technologies, 2019)
The article considers the operation and maintenance of a telecommunication system with different types of failures. A mathematical model of a telecommunication system, which is continuously tested during operation, subject to permanent and intermittent failures is developed. Mathematical equations are derived to calculate the mean times spent by the system in the operable and repair states due to the permanent and intermittent failures, and system availability using the properties of the regenerative process under arbitrary failure distributions on the infinite time horizon. The proposed analytical expressions can be used for any laws of the distribution of operating time to permanent and intermittent failures. It is also possible to use these results for the composition of distributions of time to system failure. Such composition may include the distributions related to gradual and sudden failures. A numerical example is given for calculating the mean times spent by the one-module telecommunication system in the operable and repair states, and system availability under exponential failure distributions considering permanent and intermittent failure rates. Provided calculations demonstrate that increasing the intermittent failure rate reduces the mean time spent by the system in the operable state. The obtained results allow more precisely evaluate the availability and reliability of a telecommunication system with different types of failures and can be used during the design, operation and maintenance stages of a telecommunication system.